Further psychometric evaluation of the My Family's Accessibility and Community Engagement (My FACE) tool: Mothers' ratings of perceptions of community accessibility and engagement for their child with disabilities. (July 2021) - Bourke-Taylor, Helen M.; Tirlea, Loredana; Joyce, Kahli S.
Highlights: The My Families Accessibility and Community Engagement (MyFACE) tool has good construct validity (maternal variables), is unidimensional, and has excellent internal reliability. MyFACE is a nine item scale that measures the construct of maternal perception of community accessibility and engagement for their family that included a child with a disability, as well as barriers identified by the family. The MyFACE is a clinically-relevant tool that allied health practitioners can use to identify family perceptions of accessibility and inclusion and areas for change to improve family participation in their community. This study identified maternal factors at the most influential factors on MyFACE scores. The MyFACE can be used by researchers in conjunction with any intervention that seeks to improve participation for children and families. Abstract: Background/aim: My Family's Accessibility and Community Engagement (My FACE) measures mothers' perceptions of community accessibility and engagement for families raising children with a disability. This study investigated the construct validity including the factor structure and internal reliability of the MyFace scale. Methods: Construct validity was evaluated using hypothesis testing. Structural validity was confirmed with factor analysis. Internal reliability was measured using Cronbach alpha. The nine-item MyFACE includes items representing common community destinations. A 5-point Likert scale measured perceptions of need for change and inclusion. Results: Mothers (N = 83) completed an online survey with MyFACE, maternal and childhood disability scales. Hypothesis testing revealed correlations with MyFACE: Depression Anxiety Stress Scales (DASS)-stress ( r = −.25, n = 72, p = .037), DASS-anxiety ( r = −.41, n = 70, p < .001, ), and DASS-depression ( r = −.27, n = 72, p = .023, ) scales. MyFACE scores correlated with mothers' total Health Promoting Activity Scale (HPAS) scores ( r = .40, n = 74, p < .001). HPAS was the strongest predictor of variation in MyFACE scores F (5, 66) = 5.68, p < .001. Factor analysis demonstrated unidimensionality. Internal reliability was excellent (Cronbach alpha = .80). Conclusions: The MyFACE tool is psychometrically sound. Compared to child factors, maternal mental health and health promoting behaviour had more influence on mothers' perceptions of family community accessibility and engagement. The MyFACE measures a unique, previously unmeasurable family construct.